2010
DOI: 10.1002/cphc.200900991
|View full text |Cite
|
Sign up to set email alerts
|

Donor/Acceptor Adsorbates on the Surface of Metal Oxide Nanoporous Films: A Spectroscopic Probe for Different Electron Transfer Pathways

Abstract: A composite model system which consists of a molecular donor/acceptor pair coupled to the surface of metal oxide nanoporous films is proposed to study the contribution of the surface trap states and their influence on the interfacial ET as well as charge trapping and spatial diffusion processes in films. The photophysics of this donor/acceptor system is investigated by time-resolved transient absorbance spectroscopy in the UV/Vis (347-675 nm) spectral region. Variation of the band gap allows one to disentangle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 69 publications
(122 reference statements)
0
4
0
Order By: Relevance
“…Although the signal is weak, the spectral position coincides well with the oxidized alizarin observed in earlier studies on the TiO 2 –alizarin system. In these studies an efficient ET from photoexcited alizarin to the conduction band of TiO 2 was found. …”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…Although the signal is weak, the spectral position coincides well with the oxidized alizarin observed in earlier studies on the TiO 2 –alizarin system. In these studies an efficient ET from photoexcited alizarin to the conduction band of TiO 2 was found. …”
Section: Resultsmentioning
confidence: 86%
“…This assignment is corroborated by the quantitative decay of the alizarin signal at >625 nm where the alizarin SE dominates. Such a quenching of SE is a typical feature of ET reactions. At the same time the alizarin GSB at 550–625 nm persists throughout the complete investigated time scale, demonstrating that the alizarin ground state is not completely repopulated during the investigated process. Additionally, positive absorption changes appear at >625 nm and long delay times.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations